X‐Ray Co‐Crystal Structure Guides the Way to Subnanomolar Competitive Ecto‐5′‐Nucleotidase (CD73) Inhibitors for Cancer Immunotherapy. Issue 10 (31st July 2019) - Bhattarai, Sanjay; Pippel, Jan; Meyer, Anne; Freundlieb, Marianne; Schmies, Constanze; Abdelrahman, Aliaa; Fiene, Amelie; Lee, Sang‐Yong; Zimmermann, Herbert; El‐Tayeb, Ali; Yegutkin, Gennady G.; Sträter, Norbert; et al.
Abstract: Ecto‐5′‐nucleotidase (CD73, EC 3.1.3.5) catalyzes the extracellular hydrolysis of AMP yielding adenosine, which induces immunosuppression, angiogenesis, metastasis, and proliferation of cancer cells. CD73 inhibition is therefore proposed as a novel strategy for cancer (immuno)therapy, and CD73 antibodies are currently undergoing clinical trials. Despite considerable efforts, the development of small molecule CD73 inhibitors has met with limited success. To develop a suitable drug candidate, a high resolution (2.05 Å) co‐crystal structure of the CD73 inhibitor PSB‐12379, a nucleotide analogue, in complex with human CD73 is determined. This allows the rational design and development of a novel inhibitor (PSB‐12489) with subnanomolar inhibitory potency toward human and rat CD73, high selectivity, as well as high metabolic stability. A co‐crystal structure of PSB‐12489 with CD73 (1.85 Å) reveals the interactions responsible for increased potency. PSB‐12489 is the most potent CD73 inhibitor to date representing a powerful tool compound and novel lead structure. Abstract : Co‐crystal structure enables the development of a subnanomolar ecto‐5‐nucleotidase (CD73) inhibitor . Besides outstanding potency, compound5 shows superior selectivity and extremely high metabolic stability. The new inhibitor is expected to become an important chemical probe for in vitro and in vivo studies. Small molecule CD73 inhibitors have tremendous potential for the (immuno)therapy of cancer.